Representasi Budaya Aborigin Melalui Video Musik “Milkumana” Oleh Band King Stingray - Tanto Tri Sugi Shadewo; Ferrari Lancia; Andi Banus Achir (Sinergi : Jurnal Ilmiah Multidisiplin, 2025)
This study examines the representation of Aboriginal culture in the music video Milkumana by the band King Stingray, an Australian music group known for combining elements of modern music with Yolngu culture. The purpose of this study is to understand how elements of local culture are represented visually and symbolically in the music video, and how their meanings can be interpreted through Charles S. Peirce's semiotics. The method used is a qualitative approach with Peirce's semiotic model analysis, which examines signs through three main elements: representamen, object, and interpretant. The music video Milkumana is analyzed by paying attention to visual elements such as natural landscapes, social behavior, and the use of traditional musical instruments involved in the video. The results show that Milkumana not only displays Aboriginal culture as a visual identity, but also as a form of living cultural expression. The elements of the beach and red soil represent a spiritual connection with nature and ancestors, while the scenes of helping each other reflect the social values typical of the Yolŋu community. The presence of traditional musical instruments such as the yidaki and bilma are symbols of cultural ties. Thus, Milkumana's music video is understood as a meeting place between tradition and modernity, as well as a medium of cultural resistance against the dominance of mainstream narratives. This work shows that music and visuals can be important means of maintaining, voicing, and celebrating local cultural identity. Keywords: Cultural Representation, Aboriginal, Music Video. Abstrak Penelitian ini membahas representasi budaya Aborigin dalam video musik Milkumana oleh band King Stingray, grup musik asal Australia yang dikenal menggabungkan elemen musik modern dengan budaya suku Yolngu. Tujuan penelitian ini adalah untuk memahami bagaimana unsur-unsur budaya lokal direpresentasikan secara visual dan simbolik dalam video musik tersebut, serta bagaimana makna-maknanya dapat ditafsirkan melalui semiotika Charles S. Peirce. Metode yang digunakan adalah pendekatan kualitatif dengan analisis semiotik model Peirce, yang mengkaji tanda melalui tiga elemen utama: representamen, objek, dan interpretan. Video musik Milkumana dianalisis dengan memperhatikan unsur-unsur visual seperti lanskap alam, perilaku sosial, serta penggunaan alat musik tradisional yang terlibat dalam video. Hasilnya menunjukkan bahwa Milkumana tidak hanya menampilkan budaya Aborigin sebagai identitas visual semata, tetapi juga sebagai bentuk ekspresi budaya yang hidup. Elemen pantai dan tanah merah merepresentasikan hubungan spiritual dengan alam dan leluhur, sedangkan adegan tolong-menolong mencerminkan nilai-nilai sosial khas komunitas Yolŋu. Kehadiran alat musik tradisional seperti yidaki dan bilma menjadi simbol keterikatan budaya. Dengan demikian, video musik Milkumana dipahami sebagai ruang pertemuan antara tradisi dan modernitas, sekaligus sebagai media perlawanan kultural terhadap dominasi narasi arus utama. Karya ini memperlihatkan bahwa musik dan visual dapat menjadi sarana penting dalam menjaga, menyuarakan, dan merayakan identitas budaya lokal. Kata Kunci : Representasi Budaya, Aborigin, Video Musik.